Effectiveness of platelet-rich plasma injections for the treatment of acute Achilles tendon rupture: A systematic review and meta-analysis. Issue 41 (15th October 2021) - Wang, Chenglong; Fan, Hua; Li, Yuhuan; Yun, Zhihe; Zhang, Zhuo; Zhu, Qingsan
Abstract: Background: The effect of platelet-rich plasma (PRP) on patients with acute Achilles tendon rupture is still controversial. The purpose of this systematic review is to assess the efficacy of PRP injections treating acute Achilles tendon rupture. Methods: A comprehensive electronic literature search was performed in the PubMed, Embase, Cochrane Library, and Web of Science databases to identify relevant studies that were published prior to April 29, 2021. Randomized controlled trials evaluating the efficacy of PRP injections in treating patients with acute Achilles tendon rupture were included. Statistical analyses were conducted using RevMan software. Results: Five randomized controlled trials were included in this systematic review. The results of the meta-analysis showed that PRP has positive effects on ankle dorsiflexion angle, dorsal extension strength of the ankle, and calf circumference compared with that in controls. However, the current evidence failed to show that PRP effectively improves ankle plantar flexion angle, plantar flexion strength of the ankle, and pain. Conclusions: PRP injections for the treatment of acute Achilles tendon rupture significantly improved ankle dorsiflexion angle, dorsal extension strength of the ankle, and calf circumference compared with that in controls. Additional studies with larger sample sizes, more rigorous designs and standardized protocols are needed to draw more reliable and accurate conclusions. Abstract : Supplemental Digital Content is available in the text